2021
DOI: 10.1038/s41562-021-01108-6
|View full text |Cite
|
Sign up to set email alerts
|

Mapping inequalities in exclusive breastfeeding in low- and middle-income countries, 2000–2018

Abstract: Exclusive breastfeeding (EBF)—giving infants only breast-milk for the first 6 months of life—is a component of optimal breastfeeding practices effective in preventing child morbidity and mortality. EBF practices are known to vary by population and comparable subnational estimates of prevalence and progress across low- and middle-income countries (LMICs) are required for planning policy and interventions. Here we present a geospatial analysis of EBF prevalence estimates from 2000 to 2018 across 94 LMICs mapped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 34 publications
1
34
2
1
Order By: Relevance
“…Breast milk is the sole natural and primary source of optimum sustenance for newborn babies’ physical and neurological growth and cognitive development [ 40 ]; it also boosts the child’s immune system at an early age [ 41 – 43 ]. However, it may be challenging for women to stick to EBF for six months, especially in low and lower-middle income countries like Bangladesh, where maternal malnutrition is frequent, leading to reduce breast milk production [ 44 – 48 ]. In addition, a lack of information about the benefits of EBF practice, insufficient workplace supports for mothers, and insufficient healthcare system support all contribute to mothers discontinuing the EBF practice before the recommended six-month period [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Breast milk is the sole natural and primary source of optimum sustenance for newborn babies’ physical and neurological growth and cognitive development [ 40 ]; it also boosts the child’s immune system at an early age [ 41 – 43 ]. However, it may be challenging for women to stick to EBF for six months, especially in low and lower-middle income countries like Bangladesh, where maternal malnutrition is frequent, leading to reduce breast milk production [ 44 – 48 ]. In addition, a lack of information about the benefits of EBF practice, insufficient workplace supports for mothers, and insufficient healthcare system support all contribute to mothers discontinuing the EBF practice before the recommended six-month period [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that proportion of exclusively breastfed children remains low in many lower- and middle-income countries ( 7 ). However, according to a recent geospatial analysis of EBF prevalence estimates from 2000 to 2018 across 94 low-middle-income countries (LMICS), the total prevalence of EBF increased from 27% to 39% across all countries (2000–2018) ( 8 ). It is estimated to be extrapolated to 43% by 2025 ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, according to a recent geospatial analysis of EBF prevalence estimates from 2000 to 2018 across 94 low-middle-income countries (LMICS), the total prevalence of EBF increased from 27% to 39% across all countries (2000–2018) ( 8 ). It is estimated to be extrapolated to 43% by 2025 ( 8 ). Although this could be positive progress, it falls short of the 70% goal ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…India has been slow in adopting recommended IYCF practices ( 8 ) , and the performance of MDD in India has been poor for various reasons ( 4 , 7 , 9 , 10 ) . According to the Global Burden of Disease Study, India had an estimated 19⋅1 % of children (equivalent to an estimated 5 351 900 infants under 6 months of age) who were not exclusively breastfed in 2018 ( 11 ) . Children with MDDF had low fruit, vegetable and protein-rich food consumption, and many children who met MDD also had low protein-rich food consumption ( 9 ) .…”
Section: Introductionmentioning
confidence: 99%